IMPROVING EDUCATIONAL EFFICIENCY THROUGH THE USE OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING THE SUBJECT "ELECTRONICS AND CIRCUITS" - Nurmukhamedova Tursunoy, Abdullayev Abdubakir, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The rapid advancement of information and communication technologies (ICT) has transformed various fields of education, including the teaching of electronics and circuits. This article explores the integration of modern ICT tools in the educational process, highlighting their benefits, challenges, and best practices in enhancing student engagement and comprehension in the study of electronics.